2018
DOI: 10.1002/jhbp.568
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of frailty predicts age‐related events after hepatic resection: a prospective multicenter study

Abstract: Frailty evaluated by KCL in the elderly can predict postoperative age-related events after hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 35 publications
2
61
0
2
Order By: Relevance
“…Based on their multivariate analysis, frailty was found to be an independent risk factor of age-related events after liver resection, including major cardiopulmonary complications, delirium requiring medical treatment, transfer to a rehabilitation facility, and dependency. However, the incidence of overall and major complications, 30-day mortality, and LOS did not differ between frail and non-frail patients, while the 90-day mortality rate was significantly higher in the frailty group [64] . Details of the studies utilizing frailty assessment tools to evaluate postoperative outcomes after liver resection are summarized in Table 2 [72] .…”
Section: Liver Resection and Frailtymentioning
confidence: 73%
See 2 more Smart Citations
“…Based on their multivariate analysis, frailty was found to be an independent risk factor of age-related events after liver resection, including major cardiopulmonary complications, delirium requiring medical treatment, transfer to a rehabilitation facility, and dependency. However, the incidence of overall and major complications, 30-day mortality, and LOS did not differ between frail and non-frail patients, while the 90-day mortality rate was significantly higher in the frailty group [64] . Details of the studies utilizing frailty assessment tools to evaluate postoperative outcomes after liver resection are summarized in Table 2 [72] .…”
Section: Liver Resection and Frailtymentioning
confidence: 73%
“…Data have shown that CFS can reliably distinguish patients who are going to have a complicated course and prolonged LOS while in the acute medical ward [63] . A screening tool for frailty broadly used in Japan is the Kihon Checklist (KCL) [64] . KCL is a self-reporting "yes/no" survey that can help clinicians assess the status of older individuals in several frailty domains (functional, physical, psychological, and social) [65] .…”
Section: Frailty Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising factor that also influences post-operative outcomes is patient frailty, defined as a syndrome characterized by decreased physiological reserves. Only one study has reported a specific association between frailty and PHLF [16] . However, frailty assessment is based on a self-reporting questionnaire, which could be affected by several biases.…”
Section: Introductionmentioning
confidence: 99%
“…Patient prognosis after hepatectomy is in uenced by patient age, general status, co-morbidity or organ functional reserve as well. The relationship with these parameters have been also recently examined (4)(5)(6) and, however, unexpected postoperative morbidity as hepatic failure and related mortality were still observed at this stage.…”
Section: Introductionmentioning
confidence: 99%